Southern Pacific Building
On verso: The Southern Pacific Building, planned for the service, convenience, pleasure and entertainment of the Exposition's guests, just within the Fillmore Street entrance. Comfortable rest rooms for men and women, a completely equipped ticket office and information bureau, and Sunset Theatre with splendidly illustrated lectures on the Southern Pacific country are among the features which all visitors are invited freely to enjoy. No one should miss the central exhibit where, among verdant forest surroundings, are reproduced with exquisite faithfulness many of the famous natural wonders of the Pacific Coast as well as picturesque scenes of the South and Southwest.